PENERAPAN MODEL PROBLEM BASED LEARNING SEBAGAI UPAYA UNTUK MENINGKATKAN KETERAMPILAN MENULIS TEKS EKSPOSISI DI SMP 5 PALU - Yunidar Yunidar (Program Studi Tadris Ilmu Pengetahuan Sosial (TIPS) IAIN Palu, 2023)
The study in this pap The background of this research is the lack of students' ability in writing skills, learning to write in schools in particular does not get the dominant attention so that students' ability to write is still very low. Methodologically, teachers are generally less varied in choosing the method used. This study aims to determine the increase in understanding of class VIII students of SMP 5 Palu in writing exposition texts using the Problem Based Learning (PBL) model. This type of research is Classroom Action Research (PTK) which is carried out in two cycles. Each cycle goes through four stages, namely planning, implementing actions, observing and reflecting. The research subjects were students who were active and enrolled in the even semester of the 2022/2023 school year with a total of 19 students. The data collection technique used observation and concept comprehension ability tests to collect the required data and as a benchmark for students' ability to write exposition texts based on minimum completeness criteria. Data analysis techniques using qualitative and quantitative descriptive analysis. The results showed that there was an increase in conceptual understanding from cycle I to cycle II, with the proportion of completeness 58 with an average of 72 in cycle I, to 89 with an average of 84 in cycle II, as well as the application of the Problem Based Learning model can increase students' understanding in write expository text.